Use of Arotinolol Pharmacotherapy to Treat Drug-induced Tremor: A Report of Three Cases - Lee, D. B.; Woo, Y. S.; Bahk, W. M. (Pharmacopsychiatry, 2015)
Objective: The aim of the present study is to demonstrate the effect of arotinolol on drug-induced tremor in psychiatric patients.Methods: This is a case study of three psychiatric patients with the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) diagnosis of major depressive disorder who were treated in inpatient or outpatient psychiatric settings with antidepressant or antipsychotics. Patients developed tremor. Arotinolol was started to treat the tremor.Results: Drug-induced tremor almost resolved completely. No adverse effects were observed.Conclusion: We have presented a case series of drug-induced tremors that responded well to treatment with arotinolol, which appears to be a safe and well-tolerated drug in the dose ranges used. The possible utility of arotinolol to treat drug-induced tremor deserves attention and further investigation.
Keywords: arotinolol; tremor; treatment